SCFTIR1/AFB Auxin Signaling for Bending Termination during Shoot Gravitropism. Issue 1 (27th February 2020) - Han, Huibin; Rakusová, Hana; Verstraeten, Inge; Zhang, Yuzhou; Friml, Jiří
Abstract : TIR1/AFB signaling is required and sufficient for auxin-mediated PIN3 re-polarization and shoot gravitropic bending termination.